Multichannel Staggered SAR Azimuth Processing - De Almeida, Felipe Queiroz; Younis, Marwan; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2018)
State-of-the-art and future spaceborne SAR systems increasingly often face the requirement of providing high-resolution images with reduced revisit times, requiring coverage of wide swaths. Since these are contradicting drivers in terms of system design, different alternatives for High-Resolution Wide Swath (HRWS) SAR imaging have been investigated, relying on digital beamforming (DBF) and the use of multiple receiver channels, both in elevation and azimuth dimensions. In this context, Staggered SAR, which operates with a pulse repetition frequency variation, using a single channel in azimuth proves itself as a promising alternative for covering wide continuous swaths with moderate azimuth resolution, whereas the use of multiple azimuth receiver channels bears the potential of improving the azimuth resolution over a given swath, but has yet only been applied to systems with a fixed pulse repetition frequency. This paper introduces and analyzes in detail processing techniques suitable for the combination of these techniques, leading to novel multichannel Staggered SAR imaging modes with the potential for very fine azimuth resolution over ultra-wide swaths. A system concept with 2.0 m azimuth resolution over a 400 km swath in quad-pol is provided as an example.
Keywords: Radar; Radar imaging; Spaceborne radar; Synthetic aperture radar; Digital beamforming; High resolution wide swath